Physiochemical, rheological and emulsifying properties of low methoxyl pectin prepared by high hydrostatic pressure-assisted enzymatic, conventional enzymatic, and alkaline de-esterification: A comparison study. (August 2019) - Wan, Li; Chen, Qianqian; Huang, Mengling; Liu, Fengxia; Pan, Siyi
Abstract: Low methoxyl pectin (LMP) was prepared by high hydrostatic pressure assisted enzymatic treatment (HHP-pectin). The physicochemical properties, rheological characteristics and emulsifying characteristics of LMP prepared in this manner were compared the characteristics of LMPs de-esterified using the conventional enzymatic (E-pectin) and alkaline (A-pectin) methods. The obtained results showed that under the optimal HHP conditions, the degree of methoxylation (DM) of pectin decreased from 79.91% to 37.02% within 12 min, whereas 120 min and 20 min, respectively, were required to obtain a similar DM value for the atmospheric enzymatic and alkaline treatments. Moreover, the de-esterification method had a strong influence on rheological and emulsifying properties. Compared to A-pectin, HHP-pectin and E-pectin exhibited higher viscosity, accompanied by larger average molecular weight, particle size, more negative zeta-potential and higher activation energy. All of the emulsions exhibited good stability at acidic conditions with pH 3. While the emulsion prepared using A-pectin showed the smallest particle mean diameters and better centrifugation stability, the emulsion prepared using HHP-pectin showed the best long-term emulsifying stability during 21-day storage. These results clearly demonstrated that HHP-assisted enzymatic method is a more efficient, rapid and eco-friendly alternative for pectin de-esterification, particularly for preparing LMPs with better thickening and stable emulsifying properties. Graphical abstract: Image 102602 Highlights: High hydrostatic pressure (HHP) is eco-friendly using for pectin de-esterification. HHP-assisted enzymatic de-esterification greatly shorten the reaction time. HHP de-esterified low methoxyl pectin (LMP) exhibited high Mw and viscosity. Emulsion from HHP de-esterified LMP showed good long term stability.